toner

The toner formulation with iron oxide particles and a specific hydrocarbon-treated surface enhances mold releasability and chargeability, addressing compatibility issues and reducing contamination and peeling in high-speed image forming processes.

JP7604196B2Active Publication Date: 2024-12-23CANON KK
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020199143
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-30
Publication Date
2024-12-23
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

Existing toners face issues with compatibility between transferability and fixability, leading to member contamination, image defects, and toner peeling during the fixing process, especially in high-speed machines.

Method used

A toner formulation containing binder resin, release agent, and iron oxide particles on the surface, treated with a compound having a specific hydrocarbon structure (R-SiO3/2) to enhance mold releasability and chargeability, reducing creeping discharge and improving rub-fixing properties.

Benefits of technology

The toner exhibits improved mold releasability, reduces member contamination, and minimizes toner peeling from images, ensuring high-quality image output even in high-speed operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604196000008
    Figure 0007604196000008
  • Figure 0007604196000009
    Figure 0007604196000009
  • Figure 0007604196000001
    Figure 0007604196000001
Patent Text Reader

Abstract

To provide toner in which: releasability is improved in a fixation step; member contamination can be prevented; toner peeling from images is suppressed; and a smearing property is excellent.SOLUTION: Toner contains: toner particles containing a binder resin, a mold release agent, and a coloring agent; and iron oxide particles existing on surfaces of the toner particles. The iron oxide particles have surfaces having chemical compounds with specific structures.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner used in a recording method utilizing electrophotography or the like. [Background technology]

[0002] In recent years, image forming apparatuses such as copying machines and printers are being required to operate at higher speeds, with higher image quality and greater stability, in line with the diversification of the purposes and environments in which they are used. At the same time, copying machines and printers are being made smaller and more energy-efficient, and a magnetic one-component development method using a magnetic toner, which is advantageous in these respects, is preferably used.

[0003] In the electrophotographic method, the following steps are carried out: a charging step in which an electrostatic latent image carrier (hereinafter referred to as photoconductor) is charged by a charging means, an exposure step in which the charged photoconductor is exposed to light to form an electrostatic latent image, and a development step in which the electrostatic latent image is developed with toner to form a toner image. The toner image is then transferred to a recording material with or without an intermediate transfer member, and the recording material carrying the toner image is heated, pressurized, and fixed by passing it through a nip formed by a pressure member and a rotatable image heating member, and the image is output as an image. In particular, in the magnetic one-component development method, a toner carrier (hereinafter referred to as a sleeve) with a magnetic field generating means such as a magnet roll inside is used to hold the magnetic toner, and the toner is transported to the development area for development.

[0004] In order to meet the recent trend of high image quality and energy saving, it is important to optimize each process. For image quality, it has been important to optimize the development process, which develops an electrostatic latent image with toner to form a toner image, and the transfer process, which transfers the toner image from the photoreceptor to a recording material. For energy saving, it is also important to perform sufficient fixing at low temperatures.

[0005] Focusing on the issues related to the transfer process, one of the image defects that becomes evident when there is a problem with the transfer is transfer voids. In the transfer process, the toner on the photoconductor receives a transfer bias and is transferred onto the recording medium by electrostatic attraction. During this process, toner may not be transferred and remain on the photoconductor, or the toner layer may be disturbed during transfer, causing voids or unevenness in the image. This is called transfer voids.

[0006] To date, in order to improve transferability, attempts have been made to suppress a decrease in the fluidity of the toner while externally adding iron oxide particles during toner production (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-214625 A [Patent Document 2] JP 2005-37744 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, with regard to the above-mentioned Patent Documents 1 and 2, there is still room for further study regarding compatibility between transferability and fixability. Specifically, the toners described in Patent Documents 1 and 2 do not provide sufficient release performance, which may cause contamination of the pressurizing member, image heating member, etc. in the fixing step, resulting in defective images. Furthermore, when a rubbing pressure is applied to the fixed image, such as when erasing characters written on the image with an eraser, the toner of the fixed image may peel off from the paper.

[0009] The present invention has been made in consideration of the above problems. That is, an object of the present invention is to provide a toner that has improved releasability in the fixing step, can suppress contamination of components, and has excellent rubbing fixing properties with little toner peeling from an image. [Means for solving the problem]

[0010] As a result of extensive investigations, the present inventors have found that the above problems can be solved by the toner according to the present invention described below. That is, the toner according to the present invention is a toner containing toner particles containing a binder resin, a release agent, and a colorant, and iron oxide particles present on the surfaces of the toner particles, and is characterized in that the iron oxide particles have a compound having a structure represented by the following formula (1) on their surfaces. R-SiO 3 / 2 (1) (In formula (1), R represents a hydrocarbon having one or more carbon atoms.) Effect of the Invention

[0011] According to the present invention, it is possible to provide a toner which has improved releasability in the fixing step, can suppress contamination of members, and has excellent rubbing fixing properties with little toner peeling from an image. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a diagram showing a capacitor model. [Diagram 2] This is an example of a Si absorption spectrum in near edge X-ray absorption fine structure (NEXAFS) observed for hydrophobized iron oxide particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below, but is not limited thereto. The toner according to the present invention is a toner containing toner particles containing a binder resin, a release agent, and a colorant, and iron oxide particles present on the surfaces of the toner particles, and is characterized in that the iron oxide particles have a compound having a structure represented by the following formula (1) on their surfaces. R-SiO 3 / 2 (1) (In formula (1), R represents a hydrocarbon having one or more carbon atoms.)

[0014] In the transfer process, the toner is charged positively or negatively between the photoconductor and the recording medium, and a bias of the opposite polarity is applied to the transfer material on the back side of the recording medium. Since the charged toner particles are accumulated in several layers, it is thought that creeping discharge occurs along the surface of the toner particles during the transfer process.

[0015] When strong creeping discharge occurs, the toner tends to become a reverse component due to the disturbance of the charge, and this can cause "retransfer" in which the toner on the recording medium returns to the photoconductor. For example, if retransfer occurs frequently when outputting a solid black image, transfer defects become prominent and an uneven image is formed. That is, in order to suppress transfer defects, it is necessary to suppress creeping discharge along the surface of the toner.

[0016] When considering discharge, a capacitor model can be considered, with the photoconductor and the transfer material on the back side of the recording medium as electrode plates, as shown in Figure 1. If the dielectric 12 between the electrodes 11 is toner, and its capacitance is C, C can be expressed by the following formula. C=εS / d (In the above formula, S represents the area of ​​one electrode plate, d represents the distance between the electrode plates, and ε represents the dielectric constant of the dielectric material between the electrode plates.)

[0017] A discharge occurs when the electric field applied between the electrodes 11 is large and the capacitance C of the dielectric 12 in FIG. 1 is small.

[0018] According to the above formula, the electrostatic capacitance C is proportional to the dielectric constant ε of the toner, which is a dielectric. Therefore, a toner with a high dielectric constant ε is expected to have the effect of reducing the frequency of discharge. Based on this idea, the inventors of the present invention conducted extensive research from the perspective of a substance with a high dielectric constant, and found that a significant effect can be obtained when iron oxide particles are present on the surface of the toner. The reason for this is believed to be that the presence of iron oxide particles with a high dielectric constant on the surface makes it difficult for creeping discharge to occur along the surface of the toner particles.

[0019] On the other hand, the present inventors have found that when iron oxide particles are present on the surface of the toner, contamination of the pressurizing member, image heating member, etc. occurs during the fixing process, which may cause image defects. This is believed to be due to the following reasons.

[0020] The external addition of iron oxide particles improves transferability, but because the surfaces of the iron oxide particles are hydrophilic, they have low affinity for the release agent in the toner, and the release agent is less likely to seep out around the externally added iron oxide particles during the fixing process.

[0021] Generally, a release agent with high sharp melting properties seeps onto the image surface during the fixing process. If iron oxide particles with low affinity for the release agent are present on the toner surface, they repel the release agent, resulting in a region on the image surface that is not covered with the release agent. This is thought to have led to insufficient release effect during the fixing process, leading to contamination of the components.

[0022] The image defects caused by the above-mentioned component contamination occur more prominently in high-speed machines. The reason for this is presumably related to the amount of heat given to the toner layer. The faster the image formation speed, the more difficult it is for the heat from the fixing device to be transferred to the toner, and the more toner tends to be insufficiently melted. In other words, the proportion of toner in which the amount of release agent exuded from the inside of the toner is insufficient increases, making the fixing defect more likely to occur.

[0023] In addition, when a fixed image is formed using a toner having iron oxide particles on the surface of the toner particles, and the resulting fixed image is rubbed with an eraser, the toner of the fixed image may easily peel off from the paper. This is presumably because the release agent is not well-suited around the iron oxide particles having hydrophilic surfaces, which makes the eraser less slippery, and the toner of the fixed image peels off from the paper due to the friction between the eraser and the toner. In particular, in the recesses of the paper between the paper fibers, the pressure applied to the toner during the fixing process is insufficient, so that only the surface of the toner is fixed in a molten state, and the supply of the release agent from inside the toner is insufficient. As a result, the slipperiness of the eraser is significantly worsened, and the toner becomes more likely to peel off from the paper.

[0024] In the present invention, the iron oxide particles present on the surface of the toner particles are hydrophobized so that they have a compound having the structure represented by the above formula (1). That is, the iron oxide particles present on the surface of the toner particles are hydrophobized by bonding a siloxane condensate having a hydrocarbon group having one or more carbon atoms to the surface. As a result, when the toner according to the present invention is used, member contamination due to poor fixing is suppressed and rubbing fixing property is improved.

[0025] The inventors have found that the chargeability of iron oxide particles is improved by subjecting the iron oxide particles to a silane-based surface treatment, resulting in good toner characteristics. In the present invention, a similar effect of improving chargeability can be obtained by subjecting the iron oxide particles to a surface treatment using a siloxane condensate.

[0026] On the other hand, when inorganic coupling agent condensates other than Si, such as titanates and aluminates, are used, the charging property is inferior to that when siloxane condensates are used. Therefore, when iron oxide particles that have been surface-treated with inorganic coupling agent condensates other than Si are present on the surface of toner particles, the charging of the toner is suppressed, and creeping discharge due to charging unevenness is likely to occur, and as a result, it is not possible to achieve both transferability and fixability.

[0027] Furthermore, when iron oxide particles that have been surface-treated with an inorganic compound that does not have an R group are used, the hydrophobicity is not expressed, so the effect of improving releasability is not obtained and the fixing property is not improved.

[0028] Furthermore, when the R group in the above formula (1) is not a hydrocarbon group, the surface of the iron oxide particles is not hydrophobic, and therefore, the effect of improving contamination of members and rubbing adhesion cannot be obtained.

[0029] Furthermore, when silicone oil is used as the siloxane compound for hydrophobizing the surface of the iron oxide particles, the effect of the present invention cannot be obtained. This is presumably because the fixation rate of the silicone oil to the iron oxide particles is low, and the silicone oil peels off from the iron oxide particles during the fixing process, exposing the hydrophilic iron oxide surface.

[0030] The R group in the above formula (1) preferably has 1 or more and 20 or less, more preferably 2 or more and 10 or less, and further preferably 4 or more and 6 or less carbon atoms. The smaller the number of carbon atoms in the R group in the above formula (1), the lower the affinity between the surface of the iron oxide particles and the release agent, and therefore the lower the effect of attracting the release agent to the vicinity of the iron oxide particles and the lower the effect of suppressing contamination of components due to poor fixing. On the other hand, the more carbon atoms in the R group in the above formula (1) the higher the affinity with the release agent and the greater the effect of attracting the release agent to the vicinity of the iron oxide particles. However, if the number of carbon atoms is too large, the steric hindrance of the R group makes it impossible to uniformly hydrophobize the surface of the iron oxide particles. As a result, areas that have not been hydrophobized are generated on the surface of the iron oxide particles, and the hydrophilic surface is exposed. This reduces the effect of preventing member contamination due to poor fixing and improving rubbing fixing.

[0031] It is preferable that the iron oxide particles are added to the toner surface in a sufficiently disintegrated state. If there are many secondary agglomerates of iron oxide particles coated on the surface of the toner particles, the release agent exuded during the fixing process is trapped in the agglomerated particles of the iron oxide particles, and the release effect around the iron oxide particles is not sufficiently obtained. The disintegrated state of the iron oxide particles can be evaluated by measuring the agglomerated particle size of the iron oxide particles on the toner surface using a scanning electron microscope. It is preferable that the agglomerated particle size of the iron oxide particles is 1.2 times or less than the primary particle size of the iron oxide particles.

[0032] The adhesion rate of the iron oxide particles to the toner particles is preferably 50% or more and 80% or less. If the adhesion rate of the iron oxide particles is 80% or less, the iron oxide particles are not embedded in the surface of the toner, and the exudation of the release agent is less likely to be suppressed. In addition, the effect of suppressing creeping discharge on the surface of the toner in the transfer process is highly obtained, and transfer defects can be effectively suppressed. In addition, if the adhesion rate of the iron oxide particles is 50% or more, the iron oxide particles are less likely to be liberated, and the loss of the effect of suppressing transfer defects can be suppressed. It is more preferable that the adhesion rate of the iron oxide particles to the toner particles is 60% or more and 78% or less.

[0033] The content ratio of the iron oxide particles present on the surface of the toner particles to the total amount of the toner is preferably 0.10% by mass or more and 5.00% by mass or less. If the content ratio of the iron oxide particles present on the surface of the toner particles to the total amount of the toner is 0.10% by mass or more, creeping discharge along the surface of the toner layer is significantly suppressed, the transferability is dramatically improved, and transfer omissions can be effectively suppressed. In addition, the hydrophobized iron oxide particles can attract the release agent exuded in the fixing process, so that good release properties can be obtained. Furthermore, if the content ratio of the iron oxide particles present on the surface of the toner particles to the total amount of the toner is 5.00% by mass or less, the iron oxide particles are not excessive, and the occurrence of white streaks caused by the wear of members by the liberated iron oxide particles can be suppressed. This makes it possible to suppress a decrease in the image density of a solid black image due to the occurrence of white streaks. The content ratio of the iron oxide particles present on the surface of the toner particles to the total amount of the toner is more preferably 0.50% by mass or more and 4.00% by mass or less, and even more preferably 1.00% by mass or more and 2.50% by mass or less.

[0034] In the present invention, the difference between the SP value of the binder resin and the SP value of the release agent calculated by the Fedors method is preferably 1.50 or more. Also, the difference between the SP value of the release agent calculated by the Fedors method and the SP value of the compound having the structure represented by the above formula (1) is preferably 1.20 or less.

[0035] The SP value is also called the solubility parameter, and is a numerical value used as an index of solubility and affinity, which indicates how much a substance dissolves in another substance. Materials with similar SP values ​​have high solubility and affinity, and materials with different SP values ​​have low solubility and affinity. In the present invention, the SP value is a value calculated based on the commonly used Fedors method [Poly. Eng. Sci., 14(2)147(1974)]. The unit of the SP value is (cal / cm 3 ) 1 / 2 It is.

[0036] In order for the toner heated and melted in the fixing process to exhibit a releasing effect, the release agent needs to separate and exude from the binder resin, and the exuded release agent needs to be uniformly distributed around the iron oxide particles on the toner surface.

[0037] When the SP values ​​of the binder resin, the release agent, and the compound having the structure represented by the above formula (1) each satisfy the above relationship, the release agent can be caused to seep out from inside the toner during fixing and spread around the iron oxide particles on the toner surface.

[0038] If the difference between the SP value of the binder resin and the SP value of the release agent is 1.50 or more, the release agent is easily separated from the binder resin and easily seeps onto the toner surface to exhibit a releasing effect. Furthermore, if the difference between the SP value of the release agent and the SP value of the compound having the structure represented by the above formula (1) is 1.20 or less, the release agent and the compound having the structure represented by the above formula (1) on the surface of the iron oxide particles have a high affinity. This can greatly improve the problem that the release agent that has seeped out onto the toner surface is unlikely to seep out into the surroundings of the iron oxide particles that have not been hydrophobized. Therefore, a high release effect can be obtained, and image defects caused by member contamination can be suppressed. The difference between the SP value of the binder resin and the SP value of the release agent is more preferably 2.00 to 3.50, and even more preferably 2.50 to 3.00. The difference between the SP value of the release agent and the SP value of the compound having the structure represented by the above formula (1) is more preferably 1.10 or less, and even more preferably 1.00 or less.

[0039] In the present invention, in an endothermic curve measured using a differential scanning calorimeter (DSC) with a heating rate and a cooling rate of both 100°C / min, it is preferable that the half-width of the endothermic peak in the second heating process is 4.0°C or more and 8.0°C or less. The endothermic peak in the present invention means an endothermic peak derived from a release agent. In general measurement methods using DSC, for example, in the case of a method conforming to JIS K 7121 (international standard is ASTM D3418-82), the temperature rise rate is often set to 10°C / min. Here, in terms of the printing speed of the printer, in order for the toner not to adhere to the fixing device, it is necessary for the toner to melt and the release agent to exude and exhibit the release effect in a very short time, for example, several milliseconds to several tens of milliseconds. Therefore, the present inventors conducted an investigation focusing on the ability of the release agent to separate from the binder resin and exude, and found that it is effective to change the temperature rise rate and temperature fall rate in the measurement using DSC from the general 10°C / min to 100°C / min. When the temperature rise and fall rates are 10°C / min, the measurement speed is considered to be slow considering the movement of the release agent. In other words, the parameters obtained under the measurement conditions of a temperature rise and fall rate of 10°C / min cannot explain the releasability in the fixing process of a printer, which assumes that the time during which the toner can directly receive heat from the fixing device is several milliseconds to several tens of milliseconds.

[0040] Next, a case where the first temperature increase, the temperature decrease and the second temperature increase were all performed at 100° C. / min will be described. In a combination in which the release agent and the binder resin are easily compatible, when the first heating and cooling are performed at 100°C / min, the release agent does not have time to separate sufficiently from the binder resin, and the cooling is completed while maintaining the molten plastic state after the heating. Then, when the temperature is increased again at a high rate of 100°C / min while maintaining the plastic state, the binder resin and the release agent are heated in a partially plasticized state, and an endothermic peak is obtained in which the two are mixed together, rather than an endothermic peak unique to the release agent. In this case, the more compatible the release agent and the binder resin are, the broader the half-value width becomes.

[0041] In the present invention, the half-width of the endothermic peak in the second heating process is preferably 4.0° C. or more and 8.0° C. or less, which means that the half-width of the endothermic peak in the second heating process is relatively sharp. The sharpness of the endothermic peak reflects how well the melting of the release agent and its subsequent separation from the binder resin proceed during the temperature rise process. In other words, if the release agent melts and then separates from the binder resin in a manner that sufficiently follows the fast temperature rise rate, the endothermic peak during the second temperature rise process will be sharp and the half-width will be a small value.

[0042] In the present invention, in order to solve the above-mentioned problem of contamination of components in the fixing process, it is necessary to melt the toner and exude the release agent in a very short time of several milliseconds to several tens of milliseconds. Therefore, it is important to control the half-width of the endothermic peak in the second temperature rise process within a predetermined range.

[0043] In the present invention, if the half-width of the endothermic peak in the second temperature rise process is 4.0° C. or more, it is possible to suppress a decrease in developability due to phase separation between the binder resin and the release agent in the development process and the release agent seeping out onto the toner surface. Also, if the half-width of the endothermic peak in the second temperature rise process is 8.0° C. or less, the melting of the release agent or separation from the binder resin can sufficiently follow the high-speed temperature rise, and it is possible to suppress contamination of components in the fixing process. In an endothermic curve measured using a DSC with a heating rate and a cooling rate of 100°C / min, the half-width of the endothermic peak in the second heating process is more preferably 4.0°C or more and 6.0°C or less.

[0044] In the present invention, the wettability of the iron oxide particles present on the surface of the toner particles is preferably 40% by volume or more and 80% by volume or less. The wettability of the iron oxide particles present on the surface of the toner particles is determined as follows. 0.1 g of the iron oxide particles present on the surface of the toner particles is suspended in 50 mL of a methanol / water mixed solvent, and the transmittance of light with a wavelength of 780 nm is measured. The value of the methanol concentration at which the transmittance is 50% is defined as the wettability of the iron oxide particles present on the surface of the toner particles. The wettability of the iron oxide particles present on the surface of the toner particles is more preferably 55% by volume to 60% by volume. When the wettability is within the above range, the chargeability of the iron oxide particles increases and the affinity with the release agent is improved. Therefore, a sufficient release effect can be obtained around the iron oxide particles, and image defects due to member contamination can be suppressed. The wettability can be controlled by changing the surface treatment state of the iron oxide particles. If the wettability is 40% by volume or more, the degree of hydrophobization of the iron oxide particle surface is high, and a high release effect can be obtained in the fixing process. Furthermore, if the wettability is 80% by volume or less, embedding of iron oxide particles in the surface of the toner particles can be suppressed, and problems such as transfer defects and fogging due to poor charging of the toner can be suppressed. The water / methanol wettability test method will be described later.

[0045] In the present invention, the compound having the structure represented by the above formula (1) which is present on the surface of the iron oxide particles is preferably a highly condensed compound having a high degree of condensation. When a high-molecular-weight substance in a highly condensed state is present, the hydrophobizing agent tends to be bulkier than when a low-molecular-weight substance in a low-condensed state is present. This increases the density of the hydrocarbon chains on the surface of the iron oxide particles, and the affinity with the release agent that seeps out from inside the toner during the fixing process tends to improve. This provides a significant effect in preventing member contamination due to poor release and improving rubbing fixability.

[0046] The index for evaluating the degree of condensation of the compound having the structure represented by the above formula (1) on the surface of the iron oxide particles will be described below. In the present invention, it is preferable that [Si-O-Si] / [Si-C] is 1.4 or more and 1.7 or less. Here, [Si-O-Si] / [Si-C] is defined as follows. An infrared absorption spectrum (FT-IR spectrum) is obtained for the components extracted with toluene from the iron oxide particles present on the surface of the toner particles. In the obtained FT-IR spectrum, -1 ~1040cm -1 The maximum absorption peak intensity within the range of 1240 cm is defined as [Si-O-Si]. -1 ~1280cm -1 The maximum absorption peak intensity within this range is defined as [Si-C]. In this case, the ratio of [Si-O-Si] to [Si-C] is [Si-O-Si] / [Si-C].

[0047] Hydrophobized iron oxide particles contain a certain amount of condensation product of the treatment agent that is not bonded to the iron oxide particles. By immersing 100 mg of iron oxide particles in 50 mL of toluene and leaving it for 5 hours, the condensation product of the treatment agent can be extracted into the toluene. After removing the iron oxide particles, the toluene is evaporated to dryness and the FT-IR spectrum of the extract obtained can be measured to estimate the condensation state of the hydrophobization treatment agent.

[0048] The FT-IR spectrum is measured by the ATR method. The ATR crystal is Ge, and the infrared light incidence angle is set at 45° to obtain the FT-IR spectrum. In the obtained FT-IR spectrum, the 990 cm -1 More than 1040cm -1 The maximum absorption peak intensity within the following range is defined as [Si-O-Si]. In addition, in the obtained FT-IR spectrum, the 1240 cm peak, which is thought to be due to the Si-C of siloxane, -1 More than 1280cm -1 The maximum absorption peak intensity in the following range is defined as [Si-C].

[0049] When the above FT-IR spectrum is obtained for a monomer unit obtained by hydrolysis of a silane coupling treatment agent, the peak intensity ratio [Si-O-Si] / [Si-C] is 1.3. In contrast, when the above FT-IR spectrum is obtained for a polymer obtained by fully condensing the hydrolyzate of the silane coupling treatment agent, the peak intensity ratio [Si-O-Si] / [Si-C] is 1.7.

[0050] When the condensation rate of the silane coupling agent in the toluene extract of the iron oxide particles is low, the proportion of monomer units in the extract is high, and the peak intensity ratio [Si-O-Si] / [Si-C] is close to 1.3. On the other hand, when the condensation rate of the silane coupling agent in the toluene extract of the iron oxide particles is high, the proportion of monomer units in the extract is low, and the peak intensity ratio [Si-O-Si] / [Si-C] is close to 1.7. When the ratio [Si-O-Si] / [Si-C] is 1.4 or more, the condensation rate of the silane coupling agent is high, and a high releasing effect in the fixing step can be obtained. The measurement of FT-IR spectrum by the ATR method will be described later.

[0051] Furthermore, when the iron oxide particles present on the surface of the toner particles are subjected to near edge X-ray absorption fine structure (hereinafter also referred to as NEXAFS) measurement by total electron yield method (TEY) using soft X-rays, the obtained Si absorption spectrum has peak A in the range of 1844.4 to 1844.8 eV and peak B in the range of 1846.1 to 1846.6 eV, and when the area of ​​peak A is IA, the area of ​​peak B is IB, and the number of moles of Si derived from the silane compound contained per gram of the iron oxide particles is MSi, it is preferable that IA / (IA+IB) / MSi is 40 g / mol or more and 55 g / mol or less.

[0052] By observing the near-edge X-ray absorption fine structure, it is possible to obtain information about the bonding state of the Si element in the silane compound that is bonded to the surface of the iron oxide particle. NEXAFS is a spectroscopic analysis method using soft X-rays, and is observed by the total electron yield method (TEY), which does not select the energy of the electrons generated from the sample.

[0053] Soft X-rays penetrate to a depth of about 50 nm from the surface of the sample being measured, but the electrons that can escape from the surface of the sample and are detected by NEXAFS, such as photoelectrons and Auger electrons, are limited to a depth of about 5 nm. This allows for extremely sensitive observation of the chemical bonding state of silane compounds on the surface of iron oxide particles.

[0054] An example of the Si absorption spectrum in NEXAFS observed for hydrophobized iron oxide particles is shown in Figure 2. The Si absorption spectrum has two peaks, A and B, in the range of 1840 to 1850 eV. Peak A appears on the low energy side, and peak B appears on the high energy side. Specifically, peak A appears in the range of 1844.4 to 1844.8 eV, and peak B appears in the range of 1846.1 to 1846.6 eV.

[0055] Here, when the bond between a Si atom and an O atom in a silane compound is represented as Si-OX, it is known that when X is Si, the bond between a Si atom and an O atom corresponds to peak A, and when X is Fe, the bond between a Si atom and an O atom corresponds to peak B. In other words, it can be determined that the larger peak A in the Si absorption spectrum is, the less silane compound is bonded to the surface of the iron oxide particles, and the larger peak B is, the more silane compound is bonded to the surface of the iron oxide particles.

[0056] The smaller the proportion of the silane compound chemically bonded to the iron oxide particle surface, the more highly the silane coupling agents are condensed with each other, and the bulkier the silane compound on the iron oxide particle surface becomes. The bulkier the silane compound on the iron oxide particle surface, the higher the affinity with the release agent, and the better the release effect around the iron oxide particles. In other words, by measuring the Si absorption spectrum in the above-mentioned NEXAFS, it is possible to obtain information about the ratio of bonds between the iron oxide particles and the silane coupling agent, and thereby to evaluate the bulkiness of the silane compound on the surface of the iron oxide particles.

[0057] If IA / (IA+IB) / MSi is 55 g / mol or less, the bond between the silane compound and the iron oxide particles is strong, and the exposure of the hydrophilic iron oxide surface is suppressed. If IA / (IA+IB) / MSi is 40 g / mol or more, the degree of condensation of the silane compound is high, and a high mold release effect can be obtained. It is more preferable that IA / (IA+IB) / MSi is 43 g / mol or more and 48 g / mol or less. The reason why the value of IA / (IA+IB) is divided by the value of MSi is for normalization. MSi is measured using, for example, a scanning X-ray fluorescence analyzer ZSX PrimusII (Rigaku Corporation).

[0058] The toner according to the present invention contains iron oxide particles on the surface of the toner particles, which have been hydrophobized to have a compound having the structure represented by the above formula (1). Here, the iron oxide particles can be incorporated on the surface of the toner particles by adding them to the outside of the toner particles. Examples of the iron oxide particles include iron oxides such as magnetite, maghemite, and ferrite; metals such as iron, cobalt, and nickel, or alloys of these metals with metals such as aluminum, copper, magnesium, tin, zinc, beryllium, calcium, manganese, selenium, titanium, tungsten, and vanadium, and mixtures thereof.

[0059] The iron oxide particles may have any shape, such as octahedron, hexahedron, sphere, needle, or scale, but are preferably a polyhedron having 4 or more sides, and more preferably a polyhedron having 8 or more sides.

[0060] The number average particle size (D1) of the primary particles of the iron oxide particles is preferably 0.50 μm or less, and more preferably 0.05 μm or more and 0.30 μm or less. If the number average particle diameter (D1) of the primary particles of the iron oxide particles is 0.05 μm or more and 0.30 μm or less, the primary particles are likely to adhere uniformly to the surface of the toner particles in the external addition step, and the effect of reducing fogging can be obtained. It is more preferable that the number average particle diameter (D1) of the primary particles of the iron oxide particles is 0.10 μm or more and 0.30 μm or less.

[0061] In addition, when the magnetic properties of the iron oxide particles are such that the magnetic coercive force (Hc) is 1.6 kA / m or more and 25.0 kA / m or less when 79.6 kA / m is applied, the developability tends to be improved, and this is preferable. More preferably, the magnetic coercive force (Hc) is 15.0 kA / m or more and 25.0 kA / m or less. In addition, the magnetic strength (σs) is 30 Am 2 / kg or more 90Am 2 / kg or less, and more preferably 40Am 2 / kg or more 80Am 2 / kg or less. The residual magnetization (σr) is 1.0Am 2 / kg or more 10.0Am 2 / kg or less, and more preferably 1.5Am 2 / kg or more 8.0Am 2 / kg or less.

[0062] The iron oxide particles can be produced, for example, by the following method. An aqueous solution containing ferrous hydroxide is prepared by adding an equivalent or greater amount of alkali, such as sodium hydroxide, to an aqueous solution of ferrous salt. While maintaining the pH of the prepared aqueous solution at pH 7 or higher, air is blown in and the aqueous solution is heated to 70°C or higher to carry out an oxidation reaction of the ferrous hydroxide, first producing seed crystals that will become the cores of the iron oxide powder. Next, an aqueous solution containing ferrous sulfate in an amount of about 1 equivalent based on the amount of alkali added previously is added to the slurry liquid containing the seed crystals. The reaction of ferrous hydroxide is allowed to proceed while air is blown in while maintaining the pH of the liquid at 5 to 10, and iron oxide powder is grown around the seed crystals as a core. At this time, the shape and magnetic properties of the iron oxide particles can be controlled by selecting an arbitrary pH, reaction temperature, and stirring conditions. As the oxidation reaction progresses, the pH of the liquid shifts to the acidic side, but it is preferable not to make the pH of the liquid less than 5. The iron oxide particles thus obtained can be obtained by filtering, washing, and drying them in a conventional manner. When the surface treatment is performed by a dry method, the iron oxide particles are washed, filtered, and dried, and then treated with a coupling agent. When the surface treatment is performed by a wet method, the dried particles are redispersed after the oxidation reaction is completed, or the iron oxide particles obtained by washing and filtering after the oxidation reaction are redispersed in another aqueous medium without drying, and then the coupling treatment is performed. Either the dry method or the wet method can be appropriately selected in the present invention.

[0063] Examples of coupling agents that can be used in the surface treatment of iron oxide particles include silane coupling agents, and more preferably used are silane coupling agents having a structure represented by general formula (2). R-SiX n Y m (2) [In the formula, X and Y each represent an alkoxy group, n and m each independently represent an integer of 0 to 3, where n+m=3, and R represents an alkyl group, a phenyl group, a vinyl group, an epoxy group, or a (meth)acrylic group.]

[0064] Examples of the silane coupling agent represented by the general formula (2) include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, Examples of the silane include diphenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, n-propyltrimethoxysilane, isopropyltrimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, trimethylmethoxysilane, n-hexyltrimethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, hydroxypropyltrimethoxysilane, n-hexadecyltrimethoxysilane, and n-octadecyltrimethoxysilane. In the present invention, it is preferable to use a compound in which R in the general formula (2) is an alkyl group. Among them, an alkyl group having 3 to 6 carbon atoms is preferable, and an alkyl group having 3 or 4 carbon atoms is particularly preferable. When the above-mentioned silane coupling agents are used, they can be used alone or in combination of two or more kinds. When two or more kinds are used in combination, the treatment can be performed with each coupling agent individually or simultaneously. The total amount of coupling agent used in the treatment is preferably 0.9 parts by mass or more and 3.0 parts by mass or less per 100 parts by mass of iron oxide particles, and it is important to adjust the amount of treatment agent depending on the surface area of ​​the iron oxide particles, the reactivity of the coupling agent, etc.

[0065] In the present invention, examples of the binder resin for the toner include vinyl resins and polyester resins, but there is no particular limitation and any conventionally known resin can be used. Specifically, polystyrene, styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-octyl methacrylate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-maleic acid copolymer, styrene-maleic acid ester copolymer and other styrene-based copolymers, polyacrylic acid esters, polymethacrylic acid esters, polyvinyl acetate, etc. can be used, and these can be used alone or in combination of multiple kinds. Among these, styrene-based copolymers and polyester resins are particularly preferred in terms of development characteristics, fixability, etc. The glass transition temperature (Tg) of the toner is preferably 40° C. or more and 70° C. or less. When the glass transition temperature of the toner is 40° C. or more and 70° C. or less, it is possible to improve the storage stability and durability while maintaining good fixability.

[0066] The toner according to the present invention preferably contains a charge control agent. As the charge control agent for negative charging, organic metal complex compounds and chelate compounds are effective, and specifically, monoazo metal complex compounds; acetylacetone metal complex compounds; metal complex compounds of aromatic hydroxycarboxylic acid or aromatic dicarboxylic acid, etc. are listed. Specific examples of commercially available charge control agents for negative charging include Spilon Black TRH, T-77, T-95 (manufactured by Hodogaya Chemical Co., Ltd.), BONTRON (registered trademark) S-34, S-44, S-54, E-84, E-88, E-89 (manufactured by Orient Chemical Co., Ltd.). In addition, examples of positively charged charge control agents include modified products of nigrosine and fatty acid metal salts, etc.; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts that are analogues of these, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake forming agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide compounds, etc.); metal salts of higher fatty acids; diorganotin oxides such as dibutyltin oxide, dioctyltin oxide, and dicyclohexyltin oxide; and organotin borates such as dibutyltin borate, dioctyltin borate, and dicyclohexyltin borate. Specific examples of commercially available positively charged charge control agents include TP-302, TP-415 (Hodogaya Chemical Co., Ltd.), BONTRON (registered trademark) N-01, N-04, N-07, P-51 (Orient Chemical Co., Ltd.), and Copy Blue PR (Clariant). These charge control agents can be used alone or in combination of two or more. The amount of these charge control agents used is preferably 0.1 parts by mass or more and 10.0 parts by mass or less, and more preferably 0.1 parts by mass or more and 5.0 parts by mass or less, per 100 parts by mass of the binder resin, from the viewpoint of the charge amount of the toner.

[0067] The toner particles contain a release agent. When the toner particles contain a release agent, the fixing property is improved. As the release agent, all known release agents can be used. Specifically, petroleum waxes such as paraffin wax, microcrystalline wax, petroleum wax and derivatives thereof, montan wax and derivatives thereof, hydrocarbon waxes and derivatives thereof by the Fischer-Tropsch method, polyolefin waxes such as polyethylene and polypropylene and derivatives thereof, natural waxes such as carnauba wax and candelilla wax and derivatives thereof, ester waxes, etc. Here, the derivatives include oxides, block copolymers with vinyl monomers, and graft modified products. In addition, as the ester wax, monofunctional ester waxes, bifunctional ester waxes, and polyfunctional ester waxes such as tetrafunctional and hexafunctional ester waxes can be used. The content of the release agent in the toner particles is preferably 0.5 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin. If the content of the release agent is within the above range, the fixing property is improved and the storage stability of the toner is not impaired. The release agent can be blended into the binder resin by, for example, dissolving the resin in a solvent, increasing the temperature of the resin solution, and adding and mixing the resin while stirring when producing the binder resin, or by adding the release agent during melt-kneading during toner production.

[0068] The peak temperature (hereinafter also referred to as melting point) of the maximum endothermic peak of the release agent measured by a differential scanning calorimeter (DSC) is preferably 60° C. or higher and 140° C. or lower, more preferably 70° C. or higher and 130° C. or lower. When the peak temperature (melting point) of the maximum endothermic peak is 60° C. or higher and 140° C. or lower, the toner is easily plasticized during fixing, improving the fixing property. In addition, the release agent is less likely to bleed out even when stored for a long period of time, which is preferable.

[0069] The peak temperature of the maximum endothermic peak of the release agent can be measured in accordance with ASTM D3418-82 using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments). In this case, the melting points of indium and zinc are used for temperature correction of the detector of the device, and the heat of fusion of indium is used for heat correction. Specifically, about 10 mg of the measurement sample is weighed out and placed in an aluminum pan. An empty aluminum pan is used as a reference, and the measurement is performed at a temperature rise rate of 10°C / min in the measurement temperature range of 30 to 200°C. In the measurement, the temperature is raised once to 200°C, then lowered to 30°C at 10°C / min, and then raised again at 10°C / min. The peak temperature of the maximum endothermic peak of the release agent is obtained from the DSC curve in the temperature range of 30 to 200°C during this second temperature rise process.

[0070] The colorant contained in the toner particles may be an organic pigment, an organic dye, an inorganic pigment, or the like, but is not particularly limited and any conventionally known colorant may be used.

[0071] Cyan colorants include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include the following: CI Pigment Blue 1, CI Pigment Blue 7, CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, CI Pigment Blue 60, CI Pigment Blue 62, and CI Pigment Blue 66.

[0072] Examples of magenta colorants include the following: condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinones, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. CI Pigment Red 2, CI Pigment Red 3, CI Pigment Red 5, CI Pigment Red 6, CI Pigment Red 7, CI Pigment Violet 19, CI Pigment Red 23, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 48:4, CI Pigment Red 57:1, CI Pigment Red 81:1, CI Pigment Red 122, CI Pigment Red 144, CI Pigment Red 146, CI Pigment Red 150, CI Pigment Red 166, CI Pigment Red 169, CI Pigment Red 177, CI Pigment Red 184, CI Pigment Red 185, CI Pigment Red 202, CI Pigment Red 206, CI Pigment Red 220, CI Pigment Red 221, and CI Pigment Red 254.

[0073] Yellow colorants include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include the following: CI Pigment Yellow 12, CI Pigment Yellow 13, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 62, CI Pigment Yellow 74, CI Pigment Yellow 83, CI Pigment Yellow 93, CI Pigment Yellow 94, CI Pigment Yellow 95, CI Pigment Yellow 97, CI Pigment Yellow 109, CI Pigment Yellow 110, CI Pigment Yellow 111, CI Pigment Yellow 120, CI Pigment Yellow 132, CI Pigment Yellow 136, CI Pigment Yellow 138, CI Pigment Yellow 139, CI Pigment Yellow 140, CI Pigment Yellow 141, CI Pigment Yellow 142, CI Pigment Yellow 143, CI Pigment Yellow 144, CI Pigment Yellow 145, CI Pigment Yellow 146, CI Pigment Yellow 147, CI Pigment Yellow 148, CI Pigment Yellow 149, CI Pigment Yellow 150, CI Pigment Yellow 151, CI Pigment Yellow 152, CI Pigment Yellow 153, CI Pigment Yellow 154, CI Pigment Yellow 155, CI Pigment Yellow 156, CI Pigment Yellow 157, CI Pigment Yellow 158, CI Pigment Yellow 159, CI Pigment Yellow 160, CI Pigment Yellow 161, CI Pigment Yellow 162, CI Yellow 127, CI Pigment Yellow 128, CI Pigment Yellow 129, CI Pigment Yellow 147, CI Pigment Yellow 151, CI Pigment Yellow 154, CI Pigment Yellow 155, CI Pigment Yellow 168, CI Pigment Yellow 174, CI Pigment Yellow 175, CI Pigment Yellow 176, CI Pigment Yellow 180, CI Pigment Yellow 181, CI Pigment Yellow 185, CI Pigment Yellow 191, and CI Pigment Yellow 194.

[0074] Examples of black colorants include carbon black, as well as the above-mentioned yellow colorants, magenta colorants, cyan colorants, and colorants toned to black using magnetic materials.

[0075] These colorants may be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency for OHP sheets, and dispersibility in toner particles.

[0076] When a magnetic material is used as a colorant, the magnetic material is composed mainly of magnetic iron oxide such as iron oxide or γ-iron oxide, and may contain elements such as phosphorus, cobalt, nickel, copper, magnesium, manganese, aluminum, silicon, etc. These magnetic materials have a BET specific surface area of ​​2 m2 by nitrogen adsorption method. 2 / g or more 30m 2 / g or less, and 2 / g or more 28m 2 / g or less. Also, the Mohs hardness is preferably 5 to 7. The shape of the magnetic material may be polyhedral, octahedral, hexahedral, spherical, needle-like, or scale-like, and the like, with polyhedral, octahedral, hexahedral, and spherical shapes being preferred for increasing image density because they have little anisotropy.

[0077] The content of the colorant in the toner particles is preferably 1 part by mass or more and 20 parts by mass or less relative to 100 parts by mass of the binder resin or the polymerizable monomer constituting the binder resin. When a magnetic powder is used as the colorant, the content of the magnetic powder in the toner particles is preferably 20 parts by mass or more and 200 parts by mass or less, more preferably 40 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the binder resin or the polymerizable monomer constituting the binder resin.

[0078] In the toner according to the present invention, in addition to the iron oxide particles, other external additives may be mixed and attached to the surface, if necessary. Other external additives include metal oxide fine particles (inorganic fine particles) such as silica fine particles, alumina fine particles, titania fine particles, zinc oxide fine particles, strontium titanate fine particles, cerium oxide fine particles, and calcium carbonate fine particles. In addition, composite oxide fine particles using two or more kinds of metals may be used, and two or more kinds selected from these fine particle groups in any combination may be used. Furthermore, resin fine particles and organic-inorganic composite fine particles of resin fine particles and inorganic fine particles may be used as other external additives. The other external additives more preferably include at least one selected from the group consisting of silica fine particles and organic-inorganic composite fine particles. Examples of silica fine particles include sol-gel silica fine particles prepared by a sol-gel method, aqueous colloidal silica fine particles, alcoholic silica fine particles, fumed silica fine particles obtained by a gas phase method, and fused silica fine particles. Examples of the resin particles include resin particles such as vinyl resin, polyester resin, and silicone resin.

[0079] The organic-inorganic composite fine particles include those composed of resin fine particles and inorganic fine particles. Organic-inorganic composite fine particles maintain the excellent durability and chargeability of inorganic fine particles, while the resin material component with low heat capacity hardly inhibits the coalescence of toner particles during fixing, and thus hardly inhibits fixing. Therefore, it is easy to achieve both durability and fixability. The organic-inorganic composite fine particles are preferably composite fine particles having convex portions composed of inorganic fine particles embedded in the surface of resin fine particles (preferably vinyl-based resin fine particles) which are a resin component. More preferably, the composite fine particles have a structure in which inorganic fine particles are exposed on the surface of vinyl-based resin particles. Even more preferably, the composite fine particles have a structure in which the surface of the vinyl-based resin fine particles has convex portions derived from the inorganic fine particles. Examples of inorganic fine particles constituting the organic-inorganic composite fine particles include fine particles such as silica fine particles, alumina fine particles, titania fine particles, zinc oxide fine particles, strontium titanate fine particles, cerium oxide fine particles, and calcium carbonate fine particles.

[0080] The content of other external additives in the toner is preferably 0.1 parts by mass or more and 20.0 parts by mass or less with respect to 100 parts by mass of the toner particles.

[0081] The other external additives may be subjected to a hydrophobizing treatment with a hydrophobizing agent. Examples of the hydrophobic treatment agent include chlorosilanes such as methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, t-butyldimethylchlorosilane, and vinyltrichlorosilane; Tetramethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, n-butyltrimethoxysilane, i-butyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, i-butyl alkoxysilanes such as ethyltriethoxysilane, decyltriethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-(2-aminoethyl)aminopropylmethyldimethoxysilane; silazanes such as hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexabutyldisilazane, hexapentyldisilazane, hexahexyldisilazane, hexacyclohexyldisilazane, hexaphenyldisilazane, divinyltetramethyldisilazane, and dimethyltetravinyldisilazane; Silicone oils such as dimethyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, alkyl modified silicone oil, chloro alkyl modified silicone oil, chloro phenyl modified silicone oil, fatty acid modified silicone oil, polyether modified silicone oil, alkoxy modified silicone oil, carbinol modified silicone oil, amino modified silicone oil, fluorine modified silicone oil, and terminal reactive silicone oil; Siloxanes such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane, and octamethyltrisiloxane; Examples of fatty acids and their metal salts include long-chain fatty acids such as undecylic acid, lauric acid, tridecylic acid, dodecylic acid, myristic acid, palmitic acid, pentadecylic acid, stearic acid, heptadecylic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid, and salts of the above fatty acids with metals such as zinc, iron, magnesium, aluminum, calcium, sodium, and lithium. Among these, alkoxysilanes, silazanes, and silicone oils are preferably used because they are easy to carry out hydrophobic treatment. These hydrophobic treatment agents may be used alone or in combination of two or more kinds.

[0082] The toner may contain a plurality of other external additives in order to improve the fluidity and chargeability of the toner. The number average particle size of the primary particles of the other external additives is preferably 0.030 μm or more and 0.30 μm or less.

[0083] The toner according to the present invention may further contain other additives in a small amount within a range that does not substantially adversely affect the toner, such as lubricant powders such as fluororesin powder, zinc stearate powder, and polyvinylidene fluoride powder; abrasives such as cerium oxide powder, silicon carbide powder, and strontium titanate powder; flowability imparting agents such as titanium oxide powder and aluminum oxide powder; caking inhibitors; and organic and inorganic fine particles of opposite polarity as developing property improvers. Furthermore, the surfaces of these additives may be hydrophobized before use.

[0084] The weight average particle diameter (D4) of the toner particles is preferably 3.0 μm or more and 12.0 μm or less, more preferably 4.0 μm or more and 10.0 μm or less. When the weight average particle diameter (D4) of the toner particles is 3.0 μm or more and 12.0 μm or less, good fluidity is obtained, and the latent image can be developed faithfully.

[0085] The method for producing the toner is not particularly limited, and any known method can be used. Examples of the method for producing the toner include a pulverization method, a polymerization method, such as a dispersion polymerization method, an association aggregation method, a dissolution suspension method, a suspension polymerization method, and an emulsion aggregation method.

[0086] Hereinafter, specific examples of the pulverization method for producing a toner through a melt-kneading step and a pulverization step will be given, but the method is not limited thereto. For example, a binder resin, a colorant, and a release agent, as well as a charge control agent and other additives, if necessary, are thoroughly mixed using a mixer such as a Henschel mixer or a ball mill (mixing step), and the resulting mixture is melt-kneaded using a thermal kneader such as a twin-screw kneading extruder, a heating roll, a kneader, or an extruder (melt-kneading step). The resulting molten kneaded product is cooled and solidified, then pulverized using a pulverizer (pulverization step), and classified using a classifier (classification step) to obtain toner particles. If necessary, the toner particles and an external additive are mixed in a mixer such as a Henschel mixer to obtain a toner.

[0087] Examples of mixers include the following: FM Mixer (Nippon Coke and Engineering Co., Ltd.), Super Mixer (Kawata Corporation), Rebocone (Okawahara Manufacturing Co., Ltd.), Nauta Mixer, Turbulizer, Cyclomix (Hosokawa Micron Corporation), Spiral Pin Mixer (Taiheiyo Kiko Co., Ltd.), and Lödige Mixer (Matsubo Corporation). Examples of thermal kneaders include the following: KRC kneader (Kurimoto Iron Works); Bus / Co kneader (Bus / Seconds); TEM type extruder (Toshiba Machine); TEX twin-screw kneader (Japan Steel Works); PCM kneader (Ikegai Iron Works); three-roll mill, mixing roll mill, kneader (Inoue Seisakusho); Kneadex (Mitsui Mining); M-Seconds pressure kneader, Niderruder (Moriyama Seisakusho); Banbury mixer (Kobe Steel, Ltd.).

[0088] Examples of pulverizers include the following: Counter Jet Mill, Micron Jet, Innomizer (manufactured by Hosokawa Micron Corporation); ID / Second Mill, PJM Jet Pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd.); Cross Jet Mill (manufactured by Kurimoto Iron Works Co., Ltd.); Urmax (manufactured by Nisso Engineering Co., Ltd.); SK Jet-O-Mill (manufactured by Seishin Enterprise Co., Ltd.); Cryptron (manufactured by Kawasaki Heavy Industries, Ltd.); Turbo Mill (manufactured by Turbo Kogyo Co., Ltd.); and Super Rotor (manufactured by Nisshin Engineering Co., Ltd.).

[0089] Examples of classifiers include the following: Classeal, Micron Classifier, and Spedic Classifier (manufactured by Seishin Enterprise Co., Ltd.); Turbo Classifier (manufactured by Nisshin Engineering Co., Ltd.); Micron Separator, Turboplex (ATP), and TSP Separator (manufactured by Hosokawa Micron Corporation); Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), Dispersion Separator (manufactured by Nippon Pneumatic Mfg. Co., Ltd.); and YM Microcut (manufactured by Yaskawa Shoji Co., Ltd.).

[0090] In addition, the following sieving devices may be used to sieve out coarse particles: Ultrasonic (manufactured by Koei Sangyo Co., Ltd.); Resonaseave, Gyroshifter (manufactured by Tokuju Kogyo Co., Ltd.); Vibrasonic System (manufactured by Dalton Co., Ltd.); Soniclean (manufactured by Shinto Kogyo Co., Ltd.); Turbo Screener (manufactured by Turbo Kogyo Co., Ltd.); Microshifter (manufactured by Makino Sangyo Co., Ltd.); and circular vibrating sieve. From the viewpoint of dispersibility of the external additive, the mixing time in the external addition step is preferably adjusted to within a range of 0.5 to 10.0 minutes, more preferably within a range of 1.0 to 5.0 minutes.

[0091] Next, the measurement methods for each physical property will be described. <Method for measuring the number-average particle size (D1) of primary particles of iron oxide particles> First, the iron oxide particles are observed using a transmission electron microscope. For example, a transmission electron microscope JEM2800 (JEOL Ltd.) is used for the observation, and the particle diameter can be calculated from the captured bright field image. The image capturing conditions for the JEM2800 are as follows. After thoroughly dispersing the iron oxide particles to be observed in the epoxy resin, the resin is cured for 2 days in an atmosphere at 40° C. to obtain a cured product. The cured product is cut into a thin-section sample using an ultramicrotome (Leica). Using JEM2800, a transmission image is acquired under the conditions of an accelerating voltage of 200 kV, a magnification of 100,000 times, and a size of 1024 x 1024 pixels. The obtained transmission image is binarized using image analysis software Image-Pro Plus ver.5.0, and the major axis of 100 iron oxide particles (excluding agglomerated particles) is measured, and the arithmetic average value is regarded as the number-average particle size of the primary particles.

[0092] <Method for measuring the number-average agglomerated particle size of iron oxide particles on the toner surface> The toner surface is observed under a scanning electron microscope to measure the number average aggregate particle size of the iron oxide particles, which makes it possible to confirm the disintegration state of the iron oxide particles externally added to the toner surface. For observation, a scanning electron microscope S-4800 (Hitachi High-Technologies Corporation) was used, and the particle size was calculated from the backscattered electron image. The image capturing conditions for the S-4800 were as follows:

[0093] (1) S-4800 observation conditions First, the observation conditions using the S-4800 are set as follows: acceleration voltage: 1.0 kV, emission current: 20 μA, probe current: Normal, focus mode: UHR, and WD: 3.0 mm. Detector: Select U+BSE mode and LA100, and observe the backscattered electron image in a field of view magnified up to 200,000 times. Use automatic brightness adjustment and save an image of size 1280 x 960 pixels. Take multiple images to obtain enough images to analyze at least 100 iron oxide agglomerates.

[0094] (2) Image analysis The transmitted image is binarized using image analysis software Image-Pro Plus ver.5.0, and the major axis of 100 iron oxide particles (agglomerated particles) is measured, and the arithmetic average value is regarded as the number-average agglomerated particle diameter of the iron oxide particles.

[0095] <Method for quantifying iron oxide particles present on the surface of toner particles> The amount of iron oxide particles present on the surface of the toner particles can be quantified by separating the external additive component containing the iron oxide particles from the toner particles, and then isolating and recovering the iron oxide particles from the separated external additive component. Specific methods include, for example, the following methods. (1) Place 5 g of toner in a sample bottle and add 200 mL of methanol. Then add a few drops of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, made from a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.). (2) Disperse the sample in an ultrasonic cleaner for 5 minutes to separate the external additive components. (3) The toner particles and external additives are separated by suction filtration (10 μm membrane filter). (4) Repeat steps (2) and (3) above three times. By the above operation, the external additive components are separated from the toner particles. The collected liquid is centrifuged to isolate and collect the iron oxide particles. The solvent is then removed and the toner is thoroughly dried in a vacuum dryer and the mass is measured to determine the content of iron oxide particles in 5 g of toner. This makes it possible to determine the content ratio of iron oxide particles present on the surface of the toner particles in the toner.

[0096] <Method for measuring adhesion rate of iron oxide particles> 20 g of "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7) is weighed into a 50 mL vial and mixed with 1 g of toner. Set it on the "KM Shaker" (model: V.SX, manufactured by Iwaki Sangyo Co., Ltd.), set the speed to 50, and shake for 30 seconds. As a result, the non-fixed iron oxide particles migrate from the surface of the toner particles to the dispersion liquid side. After that, using a centrifuge (trade name: H-9R, manufactured by Kokusan Co., Ltd.), separate the toner particles and the iron oxide particles that have migrated to the supernatant liquid under the condition of 16.67 s -1 for 5 minutes. Dry the separated toner by vacuum drying (40 °C / 24 hours) to make it dry and use it as a sample.

[0097] Pelletize the toner by the following press molding to make it a sample. Regarding the toner samples before and after the above treatment, perform quantitative analysis of the Fe element specific to the iron oxide particles to be analyzed by wavelength dispersive X-ray fluorescence analysis (XRF) shown below. Then, calculate the amount of iron oxide particles remaining on the surface of the toner particles without migrating to the supernatant side by the following formula (A) and use it as the fixing rate. The value of the fixing rate is the arithmetic mean value of the values obtained for 100 samples. (i) Sample preparation For sample preparation, use a sample press molding machine MAEKAWA Testing Machine (manufactured by MFG Co, LTD). Put 0.5 g of toner into an aluminum ring (model number: 3481E1), set the load to 5.0 tons, press for 1 min, and pelletize it. (ii) Example of equipment used X-ray fluorescence analyzer 3080 (manufactured by Rigaku Denki Co., Ltd.) (iii) Measurement conditions Measurement diameter: 10Φ Measurement potential, voltage 50 kV, 50 - 70 mA 2θ angle 25.12° Crystal plate LiF Measurement time 60 seconds (iv) Calculation method of the fixing rate of iron oxide particles Fixing rate of iron oxide particles (%) = (Intensity of elements derived from iron oxide particles in the toner after treatment / Intensity of elements derived from iron oxide particles in the toner before treatment) × 100 (B)

[0098] <Calculation method of SP value> The solubility parameter (SP value) is determined using the Fedors equation shown in the following formula (B). δi=(Ev / V)1 / 2=(Δei / Δvi)1 / 2 (B) Ev: Evaporation energy V: Molar volume Δei: Evaporation energy of the atom or group of i components Δvi: Molar volume of the i component atom or group The values ​​of Δei and Δvi are taken from the evaporation energies and molar volumes (25° C.) of atoms and atomic groups listed in Table 3-9 of "Basic Science of Coatings," pp. 54-57, 1986 (Maki Shoten Publishing). In formula (B), "δi" is the SP value of an atom or atomic group of the i component, and the SP value of the target substance is obtained as the sum of the SP values ​​δi of the atoms or atomic groups contained in the target substance. In the present invention, the SP value of a compound having a structure represented by formula (1) is an SP value calculated using formula (B) based on the structure of a hydrophobization treatment agent used to form a compound having a structure represented by formula (1) on the surface of iron oxide particles. The unit of SP value is (cal / cm 3 ) 1 / 2 However, 1 (cal / cm 3 ) 1 / 2 =2.046×10 3 (J / m 3 ) 1 / 2 by (J / m 3 ) 1 / 2 can be converted to units of

[0099] <Method for measuring wettability of iron oxide particles> In the wettability test of iron oxide particles using a water / methanol mixed solvent, a powder wettability tester (product name: WET-100P, manufactured by Rhesca Corporation) is used, and a methanol drop transmittance curve obtained by measurement under the following conditions and procedures is used. First, 50 mL of water is poured into the flask and the transmittance is measured. The transmittance at this time is taken as 100%, and a state in which no light is transmitted is taken as 0% transmittance. Then, the transmittance is measured while continuously adding methanol to the water to increase the methanol concentration. The methanol concentration (mass%) at which the transmitted light intensity during measurement becomes half of the transmitted light intensity when water is transmitted is taken as the wettability of the iron oxide particles.

[0100] Specifically, the transmittance is measured as follows. Place a magnetic stirrer in a beaker containing 50 mL of water. Then, weigh out 0.1 g of iron oxide particles that have been sieved through a 100 μm mesh and place it in the flask. Next, stirring is started with a magnetic stirrer at a stirring speed of 300 rpm (5 revolutions / second), and methanol is continuously added to the measurement sample liquid at a rate of 1.3 mL / min using a glass tube. At the same time, the transmittance of light with a wavelength of 780 nm is measured, and a methanol drop transmittance curve is created. The reason for using methanol as the titration solvent here is that it has little effect on the elution of the hydrophobic treatment agent used to treat the surface of the iron oxide particles, allowing for a more accurate evaluation of the surface properties of the iron oxide particles. In this measurement, for example, a glass beaker having a diameter of 5 cm may be used, and a magnetic stirrer having a spindle shape with a length of 25 mm and a maximum diameter of 8 mm and coated with Teflon (registered trademark) may be used.

[0101] <Measurement of weight-average particle size (D4) and number-average particle size (D1) of toner particles> The weight-average particle diameter (D4) and number-average particle diameter (D1) of the toner particles are measured using the following equipment and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, with an effective measurement channel count of 25,000 channels, and are calculated by analyzing the measurement data. Equipment: A precision particle size distribution measuring device using the pore electrical resistance method with a 100 μm aperture tube, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) Dedicated software: "Beckman Coulter Multisizer 3 Version 3.51" (Beckman Coulter, Inc.) The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter). Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.

[0102] The specific measurement method is as follows. (1) Pour about 200 mL of the above electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "aperture flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) About 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and about 0.3 mL of a dilution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of the above-mentioned Contaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolyte solution (5) in which the toner particles are dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume %, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight average particle size (D4). Also, when the dedicated software is set to Graph / Number %, the "Average diameter" on the Analysis / Number Statistics (Arithmetic Mean) screen is the number average particle size (D1).

[0103] <Method for measuring half-value width of toner endothermic peak> The half-value width of the endothermic peak of the toner is measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) as follows. The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. As a measurement sample, 3.0 mg of toner is precisely weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference. After holding at 20°C for 1 minute, in the first heating process, the measurement is carried out while heating the measurement sample from 30°C to 200°C at a rate of 100°C / min. Next, after holding at 200°C for 1 minute, the measurement is carried out while cooling from 200°C to 30°C at a rate of -100°C / min. Finally, after holding at 30°C for 1 minute, the measurement of the second heating process is carried out while heating from 30°C to 200°C at a rate of 100°C / min. In this second heating process, a specific heat change is obtained in the temperature range of 40°C to 200°C, and an endothermic peak resulting from the melting of the mold release agent is obtained. The melting point Tm (°C) of the mold release agent in the second heating process is the peak temperature of the maximum endothermic peak in the specific heat change curve, and the half-width of the endothermic peak is the temperature width at the midpoint between the heat quantity at the peak temperature of the maximum endothermic peak and the baseline.

[0104] <Measurement method of IR and calculation method of [Si - O - Si] / [Si - C] value> The FT - IR spectrum is measured by the ATR method using the following equipment. · Fourier transform infrared spectrometer (Spectrum One: manufactured by PerkinElmer) equipped with a Universal ATR Sampling Accessory The specific measurement procedure is as follows. The incident angle of the infrared light (λ = 5μm) is set to 45°. As the ATR crystal, a Ge ATR crystal (refractive index: 4.0) is used. Other conditions are as follows. Range Start: 4000cm -1 End: 600cm -1 Duration Scan number: 16 Resolution: 4.00cm -1

[0105] [Calculation method of hydrocarbon wax index (Ge)] (1) Install the Ge ATR crystal on the device. (2) 0.01 g of the toluene extract of the iron oxide particles is precisely weighed onto the ATR crystal. (3) Pressurize the sample with the pressure arm and measure (Force Gauge is 90). (4) The obtained FT-IR spectrum is baseline corrected using Automatic Correction. (5) 990 cm -1 ~1040cm -1 The maximum absorption peak intensity is in the range of [Si-O-Si] and 1240 cm -1 ~1280cm -1 The ratio [Si-O-Si] / [Si-C] to the maximum absorption peak intensity [Si-C] within the range is calculated. EXAMPLES

[0106] The present invention will be described in more detail below with reference to Production Examples and Examples, which are not to be construed as limiting the present invention in any way. Note that all parts in the following formulations are by weight. In the following description, Examples 26 and 29 to 35 are all reference examples.

[0107] <Production example of iron oxide particles C1> A caustic soda solution, P2O5, and SiO2 were mixed into the ferrous sulfate aqueous solution in the amounts shown below to prepare an aqueous solution containing ferrous hydroxide. Caustic soda solution: 1.00 to 1.10 equivalents to elemental iron P2O5: 0.15 mass% of phosphorus converted to iron SiO2: 0.50 mass% of silicon in terms of iron The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85° C. while blowing in air to prepare a slurry liquid containing seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry in an amount of 0.90 to 1.20 equivalents relative to the initial alkali content (sodium content of caustic soda).Then, the pH of the slurry was maintained at 7.6, and the oxidation reaction was allowed to proceed while blowing in air, to obtain a slurry containing iron oxide. After filtering and washing, the aqueous slurry was temporarily removed, and a small amount of aqueous sample was taken to measure the water content. Next, this water-containing sample was put into another aqueous medium without drying, and redispersed with a pin mill while stirring and circulating the slurry, and the pH of the redispersion liquid was adjusted to about 9.0. Then, 1.4 parts by mass of iso-butyltrimethoxysilane coupling agent was added to 100 parts by mass of iron oxide particles while stirring (the amount of iron oxide particles was calculated by subtracting the water content from the water-containing sample), and hydrolysis was performed at a liquid temperature of 45°C. After that, the mixture was thoroughly stirred and surface treatment was performed. The resulting hydrophobized iron oxide particles were filtered using a filter press, washed with a large amount of water, and then dried at 120°C for 2 hours. The resulting particles were then crushed to obtain iron oxide particles C1 having a number-average particle size (D1) of 0.26 μm.

[0108] <Production Examples of Iron Oxide Particles C2 to C8> In the production example of iron oxide particles C1, the initial pH of the redispersed slurry was set to pH (A) shown in Table 1, and after hydrolysis was performed by adding a hydrophobizing treatment agent shown in Table 1, the pH was changed to pH (B) shown in Table 1 and surface treatment was performed. Except for that, production was performed using the same device and under the same conditions as in the production of iron oxide particles C1, to obtain iron oxide particles C2 to C8.

[0109] <Manufacturing example of iron oxide particle C9> A caustic soda solution, P2O5, and SiO2 were mixed into the ferrous sulfate aqueous solution in the amounts shown below to prepare an aqueous solution containing ferrous hydroxide. Caustic soda solution: 1.00 to 1.10 equivalents to elemental iron P2O5: 0.15 mass% of phosphorus converted to iron SiO2: 0.50 mass% of silicon in terms of iron The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85° C. while blowing in air to prepare a slurry liquid containing seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry so that the amount of alkali (sodium content of caustic soda) was 0.90 to 1.20 equivalents. The pH of the slurry was then maintained at 7.6, and the oxidation reaction was allowed to proceed while blowing in air. At the end of the oxidation reaction, the pH was adjusted to 6, and the slurry was washed with water and dried. The resulting particles were crushed to obtain iron oxide particles with a number-average particle size (D1) of 0.23 μm. As a hydrophobic treatment agent, 30 parts by mass of iso-butyltrimethoxysilane was dropped into 70 parts by mass of ion-exchanged water while stirring. Then, this aqueous solution was kept at pH 5.5 and temperature 55°C, and dispersed for 120 minutes at a peripheral speed of 0.46 m / s using a dispersing blade to perform hydrolysis. Then, the pH of the aqueous solution was adjusted to 7.0, and the aqueous solution was cooled to 10°C to stop the hydrolysis reaction. Thus, an aqueous solution containing a silane compound was obtained. 100 parts by mass of iron oxide particles were placed in a high-speed mixer (product name: LFS-2 type, manufactured by Fukae Powtec Co., Ltd.), and 8.0 parts by mass of an aqueous solution containing a silane compound was added dropwise over 2 minutes while stirring at a rotation speed of 2000 rpm. Then, the mixture was mixed and stirred for 5 minutes. Next, in order to increase the adhesion of the silane compound, the mixture was dried at 40°C for 1 hour to reduce the moisture, and then the mixture was dried at 110°C for 3 hours to allow the condensation reaction of the silane compound to proceed. The mixture was then crushed and passed through a sieve with a mesh size of 100 μm to obtain iron oxide particles C9.

[0110] <Production Examples of Iron Oxide Particles C10 to C16> In the production example of iron oxide particles C9, the type of hydrophobizing treatment agent used was changed to that shown in Table 1. Otherwise, iron oxide particles C10 to C16 were produced using the same apparatus and under the same conditions as in the production of iron oxide particles C9.

[0111] <Production example of iron oxide particle C17> A caustic soda solution, P2O5, and SiO2 in an amount equivalent to 0.50 mass% silicon relative to iron element were mixed in the amounts shown below into a ferrous sulfate aqueous solution to prepare an aqueous solution containing ferrous hydroxide. Caustic soda solution: 1.00 to 1.10 equivalents to elemental iron P2O5: 0.15 mass% of phosphorus converted to iron SiO2: 0.50 mass% of silicon in terms of iron The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85° C. while blowing in air to prepare a slurry liquid containing seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry so that the amount of alkali (sodium component of caustic soda) was 0.90 to 1.20 equivalents. The pH of the slurry was then maintained at 7.6, and the oxidation reaction was allowed to proceed while blowing in air, and the pH was adjusted to 6 at the end of the oxidation reaction. The slurry was then washed with water and dried, and the resulting particles were crushed to obtain iron oxide particles with a number-average particle size (D1) of 0.23 μm. The iron oxide particles were placed in a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd.), and then 3.8 parts by mass of dimethyl silicone oil was added while being sprayed while the untreated iron oxide particles were dispersed at a rotation speed of 34.5 m / s, and the mixture was dispersed for 10 minutes. The iron oxide particles were then passed through a sieve with 100 μm openings to obtain iron oxide particles C17.

[0112] <Production example of iron oxide particles C18> Iron oxide particles C18 were obtained using the same equipment and under the same conditions as in the production example of iron oxide particles C17, except that the type and amount of hydrophobic treatment agent used was changed to 3.8 parts by mass of modified silicone oil KF-415 (manufactured by Shin-Etsu Silicones).

[0113] <Production example of iron oxide particles C19> A caustic soda solution, P2O5, and SiO2 were mixed into the ferrous sulfate aqueous solution in the amounts shown below to prepare an aqueous solution containing ferrous hydroxide. Caustic soda solution: 1.00 to 1.10 equivalents to elemental iron P2O5: 0.15 mass% of phosphorus converted to iron SiO2: 0.50 mass% of silicon in terms of iron The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85° C. while blowing in air to prepare a slurry liquid containing seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry so that the amount of alkali (sodium component of caustic soda) was 0.90 to 1.20 equivalents. Thereafter, the pH of the slurry was maintained at 7.6, and the oxidation reaction was allowed to proceed while blowing in air, and at the end of the oxidation reaction, the pH was adjusted to 6. The slurry was then washed with water and dried, and the resulting particles were crushed to obtain iron oxide particles with a number-average particle size (D1) of 0.23 μm. As a hydrophobic treatment agent, 30 parts by mass of iso-propyl triisostearoyl titanate was dropped into 70 parts by mass of ion-exchanged water while stirring. Then, this aqueous solution was kept at pH 5.5 and temperature 55°C, and dispersed for 120 minutes at a peripheral speed of 0.46 m / s using a dispersing blade to carry out hydrolysis. Then, the pH of the aqueous solution was adjusted to 7.0, and the aqueous solution was cooled to 10°C to stop the hydrolysis reaction. Thus, an aqueous solution containing a titanate compound was obtained. 100 parts by mass of iron oxide particles were placed in a high-speed mixer (product name: LFS-2 type, manufactured by Fukae Powtec Co., Ltd.), and 8.0 parts by mass of an aqueous solution containing a titanate compound was dropped over 2 minutes while stirring at a rotation speed of 2000 rpm. Then, mixing and stirring were performed for 5 minutes. Next, in order to increase the adhesion of the titanate compound, the mixture was dried at 40°C for 1 hour to reduce the moisture, and then the mixture was dried at 110°C for 3 hours to allow the condensation reaction of the titanate compound to proceed. Then, the mixture was crushed and passed through a sieve with an opening of 100 μm to obtain iron oxide particles C19.

[0114] <Production example of iron oxide particle C20> A caustic soda solution, P2O5, and SiO2 were mixed into the ferrous sulfate aqueous solution in the amounts shown below to prepare an aqueous solution containing ferrous hydroxide. Caustic soda solution: 1.00 to 1.10 equivalents to elemental iron P2O5: 0.15 mass% of phosphorus converted to iron SiO2: 0.50 mass% of silicon in terms of iron The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85° C. while blowing in air to prepare a slurry liquid containing seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry so that the amount of alkali (sodium component of caustic soda) was 0.90 to 1.20 equivalents. The pH of the slurry was then maintained at 7.6, and the oxidation reaction was allowed to proceed while blowing in air, and the pH was adjusted to 6 at the end of the oxidation reaction. The slurry was then washed with water and dried, and the resulting particles were crushed to obtain iron oxide particles with a number-average particle size (D1) of 0.23 μm. The iron oxide particles were then added to a dilute sulfuric acid solution and the pH was adjusted to 4. Next, an aluminum sulfate aqueous solution was gradually added and thoroughly mixed. With continued stirring, a sodium hydroxide solution was gradually added to adjust the pH of the suspension to 6, and the suspension was then aged. The suspension was then washed with water and dried, and the resulting particles were crushed to obtain iron oxide particles C20 having a number average particle size (D1) of 0.23 μm.

[0115] <Production example of iron oxide particle C21> In the production example of iron oxide particles C9, the type of hydrophobic treatment agent was changed to tetramethoxysilane.Other than that, production was performed using the same apparatus and under the same conditions as in the production example of iron oxide particles C9 to obtain iron oxide particles C21.

[0116] <Production example of iron oxide particle C22> In the production example of iron oxide particles C17, the type and amount of hydrophobic treatment agent used was changed to 3.8 parts by mass of hexamethyldisilazane. Otherwise, production was performed using the same apparatus and under the same conditions as in the production example of iron oxide particles C17 to obtain iron oxide particles C22.

[0117] <Production example of iron oxide particle C23> A caustic soda solution, P2O5, and SiO2 were mixed into the ferrous sulfate aqueous solution in the amounts shown below to prepare an aqueous solution containing ferrous hydroxide. Caustic soda solution: 1.00 to 1.10 equivalents to elemental iron P2O5: 0.15 mass% of phosphorus converted to iron SiO2: 0.50 mass% of silicon in terms of iron The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85° C. while blowing in air to prepare a slurry liquid containing seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry so that the amount of alkali (sodium component of caustic soda) was 0.90 to 1.20 equivalents. Thereafter, the pH of the slurry was maintained at 7.6, and the oxidation reaction was allowed to proceed while blowing in air, and the pH was adjusted to 6 at the end of the oxidation reaction. The slurry was then washed with water and dried, and the resulting particles were crushed to obtain iron oxide particles C23 with a number average particle size (D1) of 0.23 μm. Iron oxide particles C23 are iron oxide particles that have not been surface-treated.

[0118] [Table 1]

[0119] Table 2 shows the physical property values ​​of the iron oxide particles C1 to C23 produced as above, determined by the methods described above. [Table 2]

[0120] <Magnetic material (colorant) manufacturing example> Fe 2+ 88 L of 3.74 mo1 / L aqueous sodium hydroxide solution was added to 92 L of ferrous sulfate aqueous solution with a concentration of 1.79 mo1 / L, and mixed and stirred while blowing in air at 20 L / min to maintain the temperature at 89°C and the pH at 9 to 12. After mixing and stirring for 30 minutes, the slurry was filtered, washed, and dried to obtain magnetic particles.

[0121] <Production Example of Toner Particle A1> The following raw materials were prepared: Amorphous polyester resin (PES) (amorphous polyester resin obtained by condensation reaction of ethylene oxide and propylene oxide adduct of bisphenol A with terephthalic acid; Mw=9500, Tg=58°C) 100 parts by mass Magnetic material (colorant) 95 parts by weight (Number average particle size (D1) 0.20μm, magnetic properties σs: 65.9Am 2 / kg, σr:7.3Am 2 / kg, no surface treatment) Release agent B1 (behenyl behenate, melting point 75°C) 5.0 parts by weight Monoazo dye iron complex (T-77, manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts by weight These raw materials were premixed in a Henschel mixer FM10C (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.). After that, they were kneaded in a twin-screw kneading extruder (product name: PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) set at a rotation speed of 250 rpm, with the set temperature adjusted so that the direct temperature near the outlet of the kneaded material was 145°C. The obtained molten mixture was cooled, and the cooled molten mixture was coarsely pulverized with a cutter mill. The coarsely pulverized product was then finely pulverized with a turbo mill T-250 (Turbo Kogyo Co., Ltd.) at a feed rate of 25 kg / hr and an air temperature adjusted to an exhaust temperature of 38°C, and classified with a multi-division classifier utilizing the Coanda effect. As a result, toner particles A1 with a weight average particle size (D4) of 8.4 μm were obtained.

[0122] <Production Examples of Toner Particles A2 to A4> In the production example of toner particle A1, the type of release agent used was changed to that shown in Table 3. Other than that, production was carried out using the same device and under the same conditions as in the production example of toner particle A1, to obtain toner particles A2 to A4.

[0123] <Production Example of Toner Particle A5> The following raw materials were prepared: Styrene / n-butyl acrylate copolymer 1 (StAc) (styrene acrylic resin with a mass ratio of styrene and n-butyl acrylate of 78:22; Mw = 8500, Tg = 58°C) 100.0 parts by mass Magnetic material (number average particle size (D1) 0.20 μm, magnetic properties σs: 65.9 Am 2 / kg, σr:7.3Am 2 / kg, no surface treatment) 95.0 parts by weight Release agent B1 (behenyl behenate, melting point 75°C) 5.0 parts by weight Monoazo dye iron complex (product name: T-77, manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts by weight These raw materials were treated with the same apparatus and under the same conditions as in the production example of toner particles A1 to obtain toner particles A5.

[0124] <Production of Toner Particles A6 to A8> In the production example of toner particle A5, the release agent used was changed to that shown in Table 3. Other than that, the same apparatus and conditions were used as in the production example of toner particle A5 to obtain toner particles A6 to A8.

[0125] <Production Example of Toner Particle A9> Toner particles A9 were produced by an emulsion aggregation method according to the following procedure. 89.5 parts of styrene, 9.2 parts of butyl acrylate, 1.3 parts of acrylic acid, and 3.2 parts of n-lauryl mercaptan were mixed and dissolved. An aqueous solution was prepared by mixing 1.5 parts of NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) with 150 parts of ion-exchanged water, and the aqueous solution was added to the mixed solution prepared above and dispersed. An aqueous solution of potassium persulfate was prepared by mixing 0.3 parts of potassium persulfate with 10 parts of ion-exchanged water. The aqueous solution of potassium persulfate was added to the above mixed solution while slowly stirring it for another 10 minutes. After replacing with nitrogen, emulsion polymerization was carried out for 6 hours at 70° C. After the polymerization was completed, the reaction liquid was cooled to room temperature, and ion-exchanged water was added to obtain a binder resin particle dispersion liquid having a solid content concentration of 12.5 mass % and a volume-based median diameter of 0.2 μm. 100 parts of a release agent (Fischer-Tropsch wax, melting point: 77°C) and 15 parts of NEOGEN RK were mixed with 385 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 (manufactured by Joko Co., Ltd.) to obtain a release agent dispersion. The solid content of the release agent dispersion was 20% by mass. 100 parts of magnetic iron oxide particles and 10.0 parts of NEOGEN SC were mixed with 890 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 to obtain a magnetic iron oxide dispersion. 265 parts of the binder resin particle dispersion, 10 parts of the release agent dispersion, and 65 parts of the magnetic iron oxide dispersion were placed in a container, and dispersed using a homogenizer (product name: Ultra Turrax T50, manufactured by IKA Corporation). The temperature in the container was adjusted to 30°C while stirring, and 1 mol / L hydrochloric acid was added to adjust the pH to 5.0. After leaving it for 3 minutes, the temperature was raised to 50°C to generate agglomerated particles. In this state, the particle size of the agglomerated particles was measured using a Coulter Counter Multisizer 3 (registered trademark, manufactured by Beckman Coulter, Inc.). When the weight average particle size of the agglomerated particles reached 6.2 μm, 1 mol / L aqueous sodium hydroxide solution was added to adjust the pH to 8.0 to stop particle growth. Thereafter, the temperature was raised to 95° C. to fuse and spheronize the aggregated particles. When the average circularity reached 0.980, the temperature was lowered to 30° C. to obtain a toner particle dispersion. Hydrochloric acid was added to the resulting toner particle dispersion to adjust the pH to 1.5 or less, and the mixture was left to stand with stirring for 1 hour, after which the mixture was subjected to solid-liquid separation using a pressure filter to obtain a toner cake. This was reslurried in ion-exchanged water to prepare a dispersion again, and then the dispersion was subjected to solid-liquid separation using the above-mentioned filter. The reslurrying and solid-liquid separation were repeated until the electrical conductivity of the filtrate became 5.0 μS / cm or less, and finally the solid-liquid separation was performed to obtain a toner cake. The obtained toner cake was dried in a flash jet dryer (manufactured by Seishin Enterprise Co., Ltd.) The drying conditions were an inlet temperature of 90°C, a dryer outlet temperature of 40°C, and the toner cake supply speed was adjusted according to the moisture content of the toner cake so that the outlet temperature did not deviate from 40°C. Further, fine and coarse powders were removed using a multi-division classifier utilizing the Coanda effect to obtain toner particles A9. The toner particles A9 had a weight average particle size (D4) of 8.4 μm, an average circularity of 0.980, and a glass transition temperature (Tg) of 57° C.

[0126] <Production Examples of Toner Particles A10 to A12> In the production example of toner particle A5, the type and amount of release agent used were changed as shown in Table 3. Otherwise, toner particles A10 to A12 were produced using the same device and under the same conditions as in the production example of toner particle A5.

[0127] <Production Example of Toner Particle A13> In the production example of toner particles A4, the amount of release agent used was changed as shown in Table 3. Except for that, production was performed using the same device and under the same conditions as in the production example of toner particles A4, toner particles A13 were obtained.

[0128] The types of release agents used in the production of toner particles A1 to A13 and the respective physical property values ​​determined by the methods described above are shown in Table 3. The production conditions and the respective physical property values ​​determined by the methods described above for toner particles A1 to A13 are shown in Table 4.

[0129] [Table 3]

[0130] [Table 4]

[0131] <Toner 1 Manufacturing Example> Using an FM mixer (product name: FM-10B, manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts of toner particles A1 and 1 part of hydrophobic silica particles were mixed for 5 minutes at a rotation speed of 3500 rpm. In addition, in the preparation of the hydrophobic silica particles, 3-aminopropyltriethoxysilane and dimethyl silicone oil were used as hydrophobic treatment agents. Next, 2.0 parts of the iron oxide particles C1 were added to the FM mixer and mixed for 5 minutes at a rotation speed of 3000 rpm to obtain a toner mixture. Thereafter, coarse particles were removed using a 300 mesh (opening size 48 μm) sieve, and toner 1 was obtained.

[0132] <Toner 2-16 Manufacturing Examples> In the production example of toner 1, the type of iron oxide particles used was changed as shown in Table 5. Other than that, production was performed using the same device and under the same conditions as in the production example of toner 1, toners 2 to 16 were obtained.

[0133] <Production Example of Toner 17-23> In the production example of toner 1, the types of toner particles and iron oxide particles used were changed as shown in Table 5. Other than that, production was performed using the same device and under the same conditions as in the production example of toner 1, toners 17 to 23 were obtained.

[0134] <Production Example of Toner 24-29> In the production example of toner 1, the type of toner particles used was changed to toner particles A5, the type of iron oxide particles used was changed to iron oxide particles C13, and the amount of iron oxide particles used was changed as shown in Table 5. Other than that, production was performed using the same device and under the same conditions as in the production example of toner 1, toners 24 to 29 were obtained.

[0135] <Toner 30 manufacturing example> Using an FM mixer (product name: FM-10B, manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts of toner particles A5 and 1 part of hydrophobic silica particles were mixed for 5 minutes at a rotation speed of 3500 rpm. In addition, 3-aminopropyltriethoxysilane and dimethyl silicone oil were used as hydrophobic treatment agents to prepare the hydrophobic silica particles. Next, 0.1 parts of iron oxide particles C5 were added to the FM mixer, and mixed for 3 minutes at a rotation speed of 3200 rpm to obtain a toner mixture. Thereafter, coarse particles were removed using a 300 mesh (48 μm opening) sieve to obtain toner 30.

[0136] <Production Examples of Toners 31 to 34> In the production example of toner 30, the conditions for externally adding iron oxide particles were changed as shown in Table 5. Otherwise, toners 31 to 34 were produced using the same device and under the same conditions as in the production example of toner 30.

[0137] <Toner 35 Manufacturing Example> Toner 35 was obtained by changing the type of toner particles used in the production example of toner 34 to toner particle A9, except that the same device and conditions were used to produce toner 35 in the production example of toner 34.

[0138] <Comparative Example> <Production Example of Toner 36-42> In the production example of toner 1, the types of toner particles and iron oxide particles used were changed as shown in Table 5. Otherwise, production was performed using the same device and under the same conditions as in the production example of toner 1, toners 36 to 42 were obtained.

[0139] [Table 5]

[0140] Table 6 shows the physical properties of each of the toners produced above, determined by the methods described above.

[0141] [Table 6]

[0142] <Evaluation> Considering the evaluation of fixability in a high-speed machine, the HP LaserJet Enterprise M609dn was modified to a process speed of 500 mm / sec. It was also modified to be able to change the transfer bias by connecting an external power source, and the evaluation of fixation film staining, rubbing fixability, and transfer defects was performed as follows.

[0143] <Evaluation 1: Evaluation of Fixing Film Contamination> The evaluation of the staining of the fixing film was carried out in a normal temperature and humidity environment by outputting 50 sheets of solid black images in succession, and immediately outputting three sheets of solid white images, and judging the degree of staining of the solid white images. When a high-density image such as a solid black image is fixed, some of the toner that does not separate from the fixing film remains on the fixing film. If a solid white image is printed immediately after that, the toner on the fixing film transfers to the paper and appears as stains on the paper. The solid white image obtained as described above was examined under an optical microscope and evaluated according to the following criteria. The evaluation results are shown in Table 6. A:No stains. B: There is some dirt, but it is only in small spots. C: There is some dirt, but it is minor in two or more places. D: There is some dirt, with minor dirt all over the surface or obvious dirt that is easily noticeable.

[0144] <Evaluation 2: Evaluation of rubbing adhesion> The rubbing fixability was evaluated by outputting a solid black image in an environment of normal temperature and normal humidity, and measuring the rate of density reduction before and after rubbing with an eraser. The fixed image was tested for rubbing resistance with a rubber eraser (product name: MONO, manufactured by Tombow Pencil Co., Ltd.) at a load of 300 g. The density reduction rate of the solid image was measured before and after rubbing 10 times back and forth with the rubber eraser, and the rubbing fixability was evaluated according to the following criteria. The lower the reduction rate, the better the rubbing fixability. The evaluation results are shown in Table 6. A: Concentration reduction rate is 0% to 3.0% B: Concentration reduction rate is 3.1% or more and 10.0% or less C: Concentration reduction rate is 10.1% or more and 15.0% or less D: Concentration reduction rate is 15.1% or more

[0145] <Evaluation 3: Evaluation of transfer defects> Normally, when the transfer bias is high, discharge is more likely to occur, and transfer defects can be evaluated more strictly. Furthermore, in general, when a high humidity environment is used, and when cardboard that has been left in the same environment is used, transferability is poor. Cardboard (Canon, 95g / m 2 ) was used, and 1500 images of horizontal lines with a print rate of 2% were output in a single intermittent mode at normal transfer bias (0.5 kV) in a high temperature and high humidity environment (32.5°C / 80% RH). After outputting the 1500 images, one solid black image was output. After that, the transfer bias was set to 1.5 kV, and a solid black image was output. The transfer bias was changed to 1.5 kV, and a solid black image was output. The transfer defects were visually observed and evaluated according to the following criteria. The evaluation results are shown in Table 6. A: No transfer gaps were observed B: There are some unevenness in density. C: Uneven density is observed across the entire surface. D: White areas are visible on a solid black image

[0146] [Table 7] [Explanation of symbols]

[0147] 11 electrodes 12 Dielectrics

Claims

1. A toner comprising toner particles containing a binder resin, a release agent, and a colorant, and iron oxide particles present on the surfaces of the toner particles, The iron oxide particles have a compound having a structure represented by the following formula (1) on their surfaces: the rate of adhesion of the iron oxide particles to the toner particles is 50% or more and 80% or less; The toner, wherein a content ratio of the iron oxide particles to a total amount of the toner is 0.50% by mass or more and 5.00% by mass or less. R-SiO 3/2 (1) (In formula (1), R represents a hydrocarbon group having one or more carbon atoms.)

2. The SP value of the binder resin calculated by the Fedors method ((cal / cm 3 ) 1/2 ) and the SP value of the release agent ((cal / cm 3 ) 1/2 2. The toner according to claim 1, wherein the difference between the molecular weight and the molecular weight of the toner is 1.50 or more.

3. The SP value of the release agent calculated by the Fedors method (cal / cm 3 ) 1/2 ) and the SP value ((cal / cm 3 ) 1/2 3. The toner according to claim 1, wherein the difference between the molecular weight and the molecular weight of the toner is 1.20 or less.

4. The toner according to any one of claims 1 to 3, wherein in an endothermic curve measured using a differential scanning calorimeter (DSC) at a heating rate and a cooling rate of both 100°C / min, a half-value width of an endothermic peak in a second heating process is 4.0°C or more and 8.0°C or less.

5. 5. The toner according to claim 1, wherein 0.1 g of the iron oxide particles is suspended in 50 mL of a methanol / water mixed solvent, the transmittance of light with a wavelength of 780 nm is measured, and the value of the methanol concentration at which the transmittance is 50% is defined as the wettability of the iron oxide particles, and the wettability is 40 vol % or more and 80 vol % or less.

6. In the FT-IR spectrum of the component extracted with toluene of the iron oxide particles, -1 ~1040cm -1 The maximum absorption peak intensity [Si-O-Si] in the range of 1240 cm -1 ~1280cm -1 6. The toner according to claim 1, wherein the ratio [Si-O-Si] / [Si-C] to the maximum absorption peak intensity [Si-C] falling within the range of 1.4 to 1.

7.

7. When the iron oxide particles are subjected to near edge X-ray absorption fine structure (NEXAFS) measurement by a total electron yield (TEY) method using soft X-rays, the obtained Si absorption spectrum has a peak A in the range of 1844.4 to 1844.8 eV and a peak B in the range of 1846.1 to 1846.6 eV, The toner according to any one of claims 1 to 6, wherein IA / (IA+IB) / MSi is 40 g / mol or more and 55 g / mol or less, where IA is the area of ​​peak A, IB is the area of ​​peak B, and MSi is the number of moles of Si derived from the silane compound contained per gram of the iron oxide particles.

Citation Information

Patent Citations

  • Electrophotographic developer and developing device using same

    JP1998213921A

  • Electrostatic charge image developing negative charge type toner and image forming method

    JP2000214625A

  • Magnetic toner

    JP2005037744A

  • Hydrophobic magnetic iron oxide particle

    JP2005263619A

  • Method for producing basket-formed silsesquioxane

    JP2007015991A